Wool sheep and purple snails—Long‐term continuity of animal exploitation in ancient Meninx (Jerba/Tunisia). (1st September 2020) - Trixl, Simon; Ben Tahar, Sami; Ritter, Stefan; Peters, Joris
Abstract: Archaeological research at the ancient city of Meninx in Jerba, Tunisia, carried out by the Institut National du Patrimoine Tunisie and Ludwig Maximilian University of Munich (LMU) produced more than 10, 000 faunal specimens and shed light on subsistence activities spanning from the fourth century BCE until the seventh century CE. Despite its highly diverse fauna totalling at least 69 species of mammals, birds, reptiles, fish and molluscs, domestic livestock formed the mainstay of the economy at Meninx. Throughout site occupation and compared with contemporaneous sites in coastal Tunisia and Libya, sheep were of prime importance at Meninx. Diachronic demographic profiling illustrates an emphasis on the production of wool for making textiles. Together with the ubiquitous presence of crushed banded dye‐murex ( Hexaplex trunculus ) shells implying exploitation of purple dyes, we assume that both activities were integrated into a single chaîne opératoire for making purple‐dyed fabrics that were traded across the Mediterranean from Punic until Late Roman times. Zooarchaeological findings also suggest that during the Byzantine Period, this major economic activity came to a standstill, with people returning to more self‐sufficient subsistence strategies. An intersite comparison furthermore revealed that high proportions of ovicaprines are a typical feature of Punic–Roman sites in Jerba. But even at the height of Roman power in the region, autochthonous husbandry traditions continued to exist on the island, as illustrated by the fauna from Henchir Bourgou.